CDKN2A germline alterations in melanoma patients with personal or familial history of pancreatic cancer. Issue 3 (June 2018) - De Unamuno, Blanca; García-Casado, Zaida; Bañuls, José; Requena, Celia; Lopez-Guerrero, José Antonio; Nagore, Eduardo
Abstract : CDKN2A germline mutations increase the risk of melanoma development and are present in 20 and 10% of familial and multiple melanoma cases, respectively. Pancreatic cancer has been associated with CDKN2A in some populations and, accordingly, its presence in first-degree or second-degree relatives of a melanoma patient is considered as a criterion for genetic testing. In this study, we show that in an area with low melanoma incidence, CDKN2A germline mutations in patients with melanoma and personal or family history of pancreatic cancer are mainly present in the setting of familial or multiple melanoma cases. In addition, a relatively young age (⩽52 years) at pancreatic diagnosis is an additional single criterion that might also be considered. Abstract : Supplemental Digital Content is available in the text.